The effect of low- and high-dose levothyroxine on the expression, protein level, and function of P-glycoprotein in mice: The effect of levothyroxine on P-gp is variable - Tras, B; Uney, K; Eser Faki, H; Melik Parlak, T; Ozdemir Kutahya, Z (Journal of the Hellenic Veterinary Medical Society, 2023)
The study was investigated the effect of different doses of levothyroxine on the mRNA expression, protein level and function of Pgp. Mice were divided into 6 groups as control, low dose levothyroxine, high dose levothyroxine, fexofenadine, low dose levothyroxine+fexofenadine and high dose levothyroxine+fexofenadine. Mice received levothyroxine at doses of 8 and 80 µg/kg daily for 21 days. Fexofenadine was administered at dose of 40 mg/kg at the 24 h following the last administration of levothyroxine. The mRNA levels and protein level of Pgp in liver and small intestine were determined by RT-PCR and western blot analysis, respectively. Plasma concentrations of fexofenadine were determined using HPLC. Levothyroxine at low and high doses caused an insignificant increase intestinal mRNA expression of mdr1a, while high dose levothyroxine+fexofenadine caused a significant increase. Levothyroxine caused a dose-dependent decrease in intestinal mRNA expression of mdr1b. In liver, levothyroxine caused a dose-dependent increase in the mRNA expression of mdr1a. Fexofenadine significantly reduced the effect of levothyroxine on mRNA expression of mdr1a in liver. Levothyroxine increased the protein level of Pgp in liver and decrease in intestines. Low dose levothyroxine significantly increased the plasma concentration of fexofenadine. The effects of levothyroxine on the mRNA expression of mdr1a and b in small intestine and liver and protein level of Pgp varied depending on the dose, tissue type, and fexofenadine administration.